2021
DOI: 10.1002/sd.2180
|View full text |Cite
|
Sign up to set email alerts
|

Indicator‐based assessment of local and regional progress toward the Sustainable Development Goals (SDGs): An integrated approach from Romania

Abstract: In order to measure progress in achieving the Sustainable Development Goals (SDGs) by 2030, 169 targets have been approved globally. Even though interest in implementing these goals is high, many states have not yet established a set of subnational indicators to measure the implementation of the SDGs and have not completed their own assessment of progress in achieving these global goals. This study aims to measure the progress toward achieving the SDG at local and regional level in Romania by calculating the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 30 publications
0
33
0
2
Order By: Relevance
“…Sub-national regional inequalities in the European Union (EU) have registered an increasing trend during the last two decades (Amarante 2014;Benedek et al 2021). Studies examining the economic convergence showed that economic growth has been much higher in Central and Eastern European (CEE) countries with a more homogenous spatial structure and a lower level of initial GDP per capita (Benedek, Kocziszky 2015;Ivan et al 2020b).…”
Section: Growth Poles Metropolitan Areas and The New Regional Policy ...mentioning
confidence: 99%
“…Sub-national regional inequalities in the European Union (EU) have registered an increasing trend during the last two decades (Amarante 2014;Benedek et al 2021). Studies examining the economic convergence showed that economic growth has been much higher in Central and Eastern European (CEE) countries with a more homogenous spatial structure and a lower level of initial GDP per capita (Benedek, Kocziszky 2015;Ivan et al 2020b).…”
Section: Growth Poles Metropolitan Areas and The New Regional Policy ...mentioning
confidence: 99%
“…A regionális tudomány az 1970-es évektől vállalkozik ex ante típusú elemzésekre (köppel, 1979), amelyeket elsősorban terüle- ti szintű munkaerőpiaci (Hampel et al, 2007;Longi, Nijkamp, 2006;Hernandez-Murillo, Owyang, 2006) kibocsátásra és a konjuktúrára vonatkozó (Chizzolini et al, 2008;Capello, Fratesi, 2012;Hentzel et al, 2015) fenntarthatósági (Benedek et al, 2020) vizsgálatokban alkalmaznak.…”
Section: Ex Ante Pályákunclassified
“…since the 1970s, regional science has undertaken ex ante analyses (Köppel, 1979), which have been used mainly in sustainability studies (Benedek et al, 2020) of labour market output (Hampel et al, 2007;Longi, Nijkamp, 2006;Hernandez-Murillo, owyang, 2006) and conjuncture (chizzolini et al, 2008;capello, Fratesi, 2012;Hentzel et al, 2015) at the regional level.…”
Section: Ex Ante Trajectoriesmentioning
confidence: 99%